PELATIHAN DAN PENDAMPINGAN PEMBUATAN YOGHURT PADA SANTRI TPQ BAITUL KHOIR - Khusnia Agustin; Nuril Hidayati; Trio Ageng Prayitno (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
The purpose of this service activity is to training and mentoring TPQ Baitul Khoir students in making yogurt as a provision for future businesses. The method of service implementation includes Observation, Planning, Implementation, Evaluation, and Reflection (OPIER). Observations were made through field reviews and direct interviews with the guardians of TPQ Baitul Khoir students. Planning is made based on the results of observations. The implementation of the service is carried out based on the plans that have been made. Evaluation is carried out to determine the impact of the implementation of the service. Reflection to analyze obstacles and follow-up plans for the next service activity. The results of the service show that the students of TPQ Baitul Khoir can make yogurt. Santri TPQ Baitur Khoir is very enthusiastic and passionate about making yogurt. The obstacle experienced was that the service area was relatively narrow, thereby reducing the space for the service team and participants. Thus, this service concludes that service activities can train and assist TPQ Baitul Khoir students in making yogurt as a business provision in the future when they want to earn income from a business.